Comparison Matrix-Associated Stem Cell Transplantation (MAST) with Autologous Matrix Induced Chondrogenesis plus Peripheral Blood Concentrate (AMIC+PBC) in Chondral Lesions at the Ankle - Matched-Patient Analysis - Martinus Richter MD, PhD; Stefan Zech MD; Stefan A. Meissner; Issam Naef (Foot & Ankle Orthopaedics, 2020)
Category: Ankle Introduction/Purpose: 2016, the local government authorities re-categorized MAST, i.e. the included BMAC for impregnation of the matrix, as stem call manufacturing and heterologous transplantation. Consequently, MAST and all other procedures including BMAC were not ‘subject to disclosure’ as before but ‘subject to authorization’. Therefore, the authors´ institution was not authorized to perform MAST after July 16, 2016. The authors´ institution changed the treatment of chondral lesions by replacing BMAC as part of MAST to Peripheral Blood Concentrate (PBC) resulting in AMIC+PBC.The aim of the study was to compare MAST with AMIC+PBC in chondral lesions at the ankle. Methods: In a matched-patient clinical follow-up study, patients with chondral lesion at the ankle that were treated with AMIC+PBC from July 17, 2016 to May 31, 2017, and patients that were treated with MAST from April 1, 2009 to July 15, 2016 were included and compared. Size and location of the chondral lesions and the Visual-Analogue-Scale Foot and Ankle (VAS FA) before treatment and at follow-up were analysed. Bone Marrow Aspirate Concentrate (BMAC) was used for MAST and Peripheral Blood Concentrate (PBC) for AMIC+PBC to impregnate a collagen I/III matrix (Chondro-Gide, Wollhusen, Switzerland) that was fixed into the chondral lesion with fibrin glue. Results: One hundred and twenty-nine patients with 136 chondral lesions were included in both groups. The chondral lesions were located as follows (MAST/AMIC+PBC, n (%)), medial talar shoulder only, 59 (43)/62 (46); lateral talar shoulder only, 44 (32)/42 (31); medial and lateral talar shoulder, 7 (10)/7 (10); tibia, 19 (14)/18 (13). The lesion size was 1.6/1.8cm2 on average and VAS FA was 46.9/45.7 (MAST/AMIC+PBC). For MAST/AMIC+PBC groups, 107 (83%)/105 (81%) with 112/110 previous chondral lesions completed the defined 2-year-follow-up after 24.4/23.8 months on average. VAS FA improved to 82.3/79.8 (MAST/AMIC+PBC). No parameter significantly differed between MAST and AMIC+PBC groups. Conclusion: MAST and AMIC+PBC as part of a complex surgical approach led to improved and high validated outcome scores in 2-year-follow-up. MAST and AMIC+PBC showed similar results. No method related complications were registered.